(untitled) (International Journal of Engineering and Computer Science, 2014)
A Wireless Sensor Network (WSN) consists of distributed autonomous sensors to monitor physical or environmental conditions and to cooperatively pass their data through the network to a main location. Each node and sensor is capable of computation, communication and sensing. Size and cost constraints on sensor nodes result in corresponding constraints on resources such as energy and memory. Sensor Node battery capacity management improves to a considerable extent the challenges of recharging nodes and prolonging WSN lifetime. The energy allocation according to wireless node charge level along with energy harnessing, Optimal decision of node sampling rate and Time determination of natural energy utilization are methods by which Node battery capacity can be maintained in an energy efficient way thereby saving energy during WSN working and data transmission by sensor nodes . This paper gives an overview of energy saving in WSN, objectives leading to conservation of power in Wireless nodes, challenges and constraints in WSN working and methods to maintain battery reserves of WSN sensor nodes.